“Campaña de control de Sigatoka Negra (Mycosphaerella fijiensis Morelet) en la Hacienda la Elvira del año 2017” - De los Angeles Moposita, Jenny Lucia (2018)
SUMMARY Black Sigatoka, caused by the fungus Mycosphaerella fijiensis is considered the most serious threat to the production of banana crops because of its highly destructive effects on the foliage of plants and the serious consequences this has for the quantity and quality of the fruit. . The pathogen rapidly destroys leaf tissue; As a result, photosynthesis is reduced, and plant growth and production are affected. In the absence of control measures, the disease can reduce the weight of the cluster by up to 50% and cause 100% production losses due to deterioration in fruit quality (length and thickness). All the stages of the disease are found in a plantation. The initial symptoms are almost imperceptible striae, reaching the more advanced stages with symptoms of necrosis or burning of the leaf area, which reduces the photosynthetic capacity of the leaves. KEYWORDS Black Sigatoka, Epidemiology, Fungicides, Cultivars.